Geographical variation in the incidence of type 1 diabetes in the Nordic countries: A study within NordicDiabKids. Issue 2 (17th November 2019) - Samuelsson, Ulf; Westerberg, Lars; Aakesson, Karin; Birkebæk, Niels H.; Bjarnason, Ragnar; Drivvoll, Ann K.; Skrivarhaug, Torild; Svensson, Jannet; Thorsson, Arni; Hanberger, Lena; ,
Abstract: Background: The incidence of type 1 diabetes (T1D) is high in the Nordic countries with geographic differences between as well as within countries. Objective: To describe the geographical distribution of the incidence of T1D among children in four Nordic countries, an area where the population is considered genetically similar. Methods: Data on children 0 to 14 years of age and diagnosed with T1D 2006 to 2011 was collected from four Nordic national pediatric quality diabetes registries. Data included year of diagnosis (2006‐2011), sex, and age at diagnosis. Figures for number of children at risk during 2006 to 2011—as well as total population, proportion with foreign background and size of populated areas of geographic regions—were collected from official statistics. Results: The total incidence during the study period for all four countries was 35.7/100 000 person years but differed between the countries (range 18.2‐44.1; P  < .001). The incidence difference between the countries was most obvious in the highest age group, 10 to 14 years of age, whereas there was no difference in the youngest age group 0 to 5 years of age. Iceland had similar incidence in the entire country, whereas the other countries had areas with different incidence. Densely populated areas, such as major cities, had the lowest incidence. Conclusion: The incidence of T1D differed between the Nordic countries and also between the neighboring countries and generally decreased with population density. This indicates that environmental factors may contribute to the level of incidence of T1D.